Anti- Toxoplasma gondii antibodies in patients with beta-hemoglobinopathies: The first report in the Americas - Ferreira, Marina Neves [UNESP]; Bonini-Domingos, Claudia Regina [UNESP]; Fonseca Estevão, Isabeth [UNESP]; De Castro Lobo, Clarice Lopes; Souza Carrocini, Gisele Cristina [UNESP]; Silveira-Carvalho, Aparecida Perpétuo; Ricci, Octávio; De Mattos, Luiz Carlos; Brandão De Mattos, Cinara Cássia (Springer Nature, 2017)
Background In Brazil, there have been no previous studies of Toxoplasma gondii infection in sickle cell anemia patients and carriers of severe forms of beta-thalassemia. This study evaluated T. gondii infection in patients with beta-hemoglobinopathies. Methods A total of 158 samples, 77 (48.7%) men and 81 (51.3%) women, were evaluated. Three groups were formed: G1 (85 patients with sickle cell disease); G2 (11 patients with homozygous beta-thalassemia; G3 (62 patients with heterozygous beta-thalassemia). ELISA was employed to identify anti-T. gondii IgM and IgG antibodies, and molecular analysis was performed to determine beta-hemoglobin mutations. Fisher's exact test was used to compare frequencies of anti-T. gondii IgM and IgG antibodies in respect to gender and age. Results Anti-T. gondii IgG antibodies were found in 43.5% of individuals in G1, 18.1% in G2 and 50% in G3. All samples from G1 and G2 were seronegative for anti-T. gondii IgM antibodies, but 3.2% from G3 were seropositive. Considering anti-T. gondii IgG antibodies, no statistical significant differences were found between these groups nor in seroprevalence between genders within each group. Despite this, comparisons of the mean ages between G1, G2 and G3 were statistically significant (G2 vs. G1: p value = 0.0001; G3 vs. G1: p-value <0.0001; G3 vs. G2: p-value = 0.0001). Conclusion A comparison by age of patients with sickle cell anemia showed a trend of lower risk of infection among younger individuals. Therefore, this study demonstrates that T. gondii infection occurs in patients with beta-thalassemia and sickle cell anemia in Brazil as seen by the presence of anti-T. gondii IgM and IgG antibodies.
Keywords: Beta hemoglobinopathies; Beta-thalassemia; Sickle cell disease; Toxoplasma gondii; Toxoplasmosis